Pre-Operative Predicting Model of Early Tumor Recurrence outside the Milan Criteria for Hepatocellular Carcinoma - Hung, Hao-Chien; Lee, Jin-Chiao; Wang, Yu-Chao; Cheng, Chih-Hsien; Wu, Tsung-Han; Lee, Chen- Fang; Wu, Ting-Jung; Chou, Hong-Shiue; Chan, Kun- Ming; Lee, Wei-Chen (Archives of Clinical and Biomedical Research, 2023)
Purpose: Liver resection is a primary curative treatment for early stage hepatocellular carcinoma (HCC), but the outcomes are impeded by early tumor recurrence. This study aimed to establish a prediction model which could predict tumor recurrence outside the Milan criteria prior to liver resection. Methods: A cohort of 891 HCC patients who had curative liver resections were reviewed. HCC recurrence was divided into 4 groups: early recurrence inside the Milan criteria (ER-MI), early recurrence outside the Milan criteria (ER-MO), late recurrence inside the Milan criteria (LR-MI), and late recurrence outside the Milan criteria (LR-MO). The risk factors of ER-MO were analyzed to establish a prediction model. Results: During a median follow-up of 83.4 months, 589 (66.1%) patients developed recurrent HCC. Among 589 patients, 276 (31.0%), 86 (9.6%), 46 (5.2%) and 181(23.3%) patients were in ER-MO, ER-MI, LR-MO and LR-MI groups, respectively. In multivariate analysis of pre-operative factors, large tumors, non-single tumors, high α-fetoprotein level, high neutrophil-to-lymphocyte ratio and high indocyanine green retention were the independent predictors of ER-MO. By adjusting the weight of independent risk factors into scores and stratifying patients into class I, II, III and IV according to score 0, 2-6, 7-10 and ≥11, ER-MO events at 24 months were 12.5%, 22.5%, 45.4% and 66.3% for class I, II, III and IV, respectively (P< 0.05). Conclusions: A risk scoring model was built and could predict ER-MO based on pre-operative factors. This scoring model would be helpful for sharing the decision marking of liver resection or primary liver transplantation with the patients.